Impact of Environmental, Demographical and Personal Factors on Auditors’ Ethical Decision Making in Nigeria - Fagbemi, Temitope Olamide (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2020)
This research introduces organization and personal dimensions to the study of ethics amid the adverse reactions of the users of the financial statements to a business fiasco. Using survey research design, a sample of one hundred and thirty-eight audit firms was taken while Probit analysis was used in testing the propositions made. Findings indicate that knowledge of the client industry and government policy are vital in shaping ethical decision making. It was concluded that environmental uncertainties and personal orientation of the auditor offers explanations to the dilemma and decision making of the auditor. Thus, it is suggested that a critical review of audit personnel characteristics and the technological environment would be a step in the right direction if the ethical dilemma is to be minimized.